Taxon-Specific Proteins of the Pathogenic Entamoeba Species E. histolytica and E. nuttalli - König, Constantin; Honecker, Barbara; Wilson, Ian W.; Weedall, Gareth D.; Hall, Neil; Roeder, Thomas; Metwally, Nahla Galal; Bruchhaus, Iris (Frontiers in Cellular and Infection Microbiology, 2021)
The human protozoan parasite Entamoeba histolytica can live in the human intestine for months or years without generating any symptoms in the host. For unknown reasons, amoebae can suddenly destroy the intestinal mucosa and become invasive. This can lead to amoebic colitis or extraintestinal amoebiasis whereby the amoebae spread to other organs via the blood vessels, most commonly the liver where abscesses develop. Entamoeba nuttalli is the closest genetic relative of E. histolytica and is found in wild macaques. Another close relative is E. dispar, which asyptomatically infects the human intestine. Although all three species are closely related, only E. histolytica and E. nuttalli are able to penetrate their host’s intestinal epithelium. Lineage-specific genes and gene families may hold the key to understanding differences in virulence among species. Here we discuss those genes found in E. histolytica that have relatives in only one or neither of its sister species, with particular focus on the peptidase, AIG, Ariel, and BspA families.